1987
DOI: 10.1093/infdis/155.6.1282
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein F (Porin) Preparation of Pseudomonas aeruginosa as a Protective Vaccine Against Heterologous Immunotype Strains in a Burned Mouse Model

Abstract: Outer membrane (OM) protein F (porin) was purified by extraction from polyacrylamide gels of cell envelope proteins of the Pseudomonas aeruginosa PA01 strain. Mice were immunized intramuscularly with 10 micrograms of protein F preparation on days 1 and 14 and then subjected to burn and challenge on day 28. Protein F immunization afforded significant protection above that provided by PA01 lipopolysaccharide (LPS) immunization against subsequent challenge with six of six heterologous LPS immunotype strains of P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 29 publications
2
85
1
Order By: Relevance
“…Possession of the aerobactin system by pathogenic bacteria has been implicated as a virulence factor by epidemiological evidence (Montgomerie et al, 1984;Carbonetti et al, 1986;Linggood et al, 1987;Jacobson et al, 1988) and by studies using laboratory strains in experimental infections (Williams, 1979). We believe, however, that this paper contains the first report in which the aerobactin genes alone, isolated from other potential virulence factors encoded, for example, by ColV plasmids, have been studied in the genetic background of a clinical E. coli isolate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possession of the aerobactin system by pathogenic bacteria has been implicated as a virulence factor by epidemiological evidence (Montgomerie et al, 1984;Carbonetti et al, 1986;Linggood et al, 1987;Jacobson et al, 1988) and by studies using laboratory strains in experimental infections (Williams, 1979). We believe, however, that this paper contains the first report in which the aerobactin genes alone, isolated from other potential virulence factors encoded, for example, by ColV plasmids, have been studied in the genetic background of a clinical E. coli isolate.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli (O'Brien & Gibson, 1970) and other members of the Enterobacteriaceae (Pollock et al, 1970;Perry & San Clemente, 1979) synthesize the phenolic siderophore enterochelin (enterobactin), but some clinical isolates of enteric bacteria also possess a second high-affinity iron-uptake system mediated by the hydroxamate siderophore aerobactin (Braun, 1981 ;Warner et al, 1981 ;Roberts et al, 19866;Martinez et al, 1987). The ability to make and use aerobactin increased the virulence of E. coli K12 strains in experimental infections (Williams, 1979), and a number of epidemiological studies showed significantly higher incidence of the aerobactin system among bacteria isolated from extraintestinal infections than among isolates from the faeces of healthy individuals (Montgomerie et al, 1984;Carbonetti et al, 1986;Linggood et al, 1987;Jacobson et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to overcome these problems some researchers have considered OMPs as immunotherapeutic agents, since they are non-toxic and are antigenically conserved among serotypes (Mutharia et al, 1982;Anwar et al, 1985). Gilleland et al (1 984) reported that antibodies to protein F offered protection against intraperitoneal challenge with laboratory strains of P. aeruginosa and, more recently, Matthews-Greer and Gilleland (1987) demonstrated protection with purified protein F against challenge with six heterologous LPS Fisher-Devlin immunotypes in a burned mouse model. The ability of IRMPs and other major OMPs, individually or in combination, to protect animals against challenge with different serotypes of P. aeruginosa remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that active immunization with outermembrane (OM) protein F of P. aeruginosa affords protection from P. aeruginosa in a number of animal models, including a rat model of chronic pulmonary infection (Gilleland et al, 1988, a murine acute infection model (Gilleland et al, 1984) and a murine burn wound sepsis model (Matthews-Greer & Gilleland, 1987;Matthews-Greer et al, 1992). Since protein F purified from bacteria is not suitable for human vaccination due to its contamination with LPS and its requirement for detergent to prevent its denaturation into an insoluble precipitate, peptides of protein F, representing surface-exposed linear B cell epitopes, were identified and synthesized (Hughes et al, 1992 ;.…”
Section: Introductionmentioning
confidence: 99%